2009
DOI: 10.1007/s00020-009-1703-0
|View full text |Cite
|
Sign up to set email alerts
|

On the Eigenfunctions of No-Pair Operators in Classical Magnetic Fields

Abstract: We consider a relativistic no-pair model of a hydrogenic atom in a classical, exterior magnetic field. First, we prove that the corresponding Hamiltonian is semi-bounded below, for all coupling constants less than or equal to the critical one known for the Brown-Ravenhall model, i.e., for vanishing magnetic fields. We give conditions ensuring that its essential spectrum equals [1, ∞) and that there exist infinitely many eigenvalues below 1. (The rest energy of the electron is 1 in our units.) Assuming that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2103
2103

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…x , Ê) with fixed sign and satisfying |∇F | a, we have iy ∈ ̺(D A + iα · ∇F ), The bound (A.2) is essentially well-known. For instance, its proof given in [22] for classical vector potentials works for quantized ones as well. Next, we set for all ϕ ∈ D 0 .…”
Section: Appendix a Estimates On Functions Of The Dirac Operatormentioning
confidence: 99%
“…x , Ê) with fixed sign and satisfying |∇F | a, we have iy ∈ ̺(D A + iα · ∇F ), The bound (A.2) is essentially well-known. For instance, its proof given in [22] for classical vector potentials works for quantized ones as well. Next, we set for all ϕ ∈ D 0 .…”
Section: Appendix a Estimates On Functions Of The Dirac Operatormentioning
confidence: 99%
“…More precisely, we shall prove a suitable bound on the spatial exponential localization of spectral subspaces corresponding to energies below the ionization threshold which applies to all γ γ c . This localization estimate is derived in Section 4 by adapting and extending ideas from [1,23,24]. We remark that by now we are able to improve the localization estimates of [24] thanks to some more recent results of [18] collected in Proposition 3.3.…”
Section: Introductionmentioning
confidence: 75%
“…An error in the constant he obtained was corrected by Walter [23]. (7) The 3-dimensional magnetic case -for a rather big class of magnetic fields -was treated by Matte and Stockmeyer [14]. They showed that the critical constant is not lowered by an intricate resolvent method.…”
Section: Notation Formulation Of the Problem And Main Resultsmentioning
confidence: 99%
“…The generality of their result is paid for by the absence of an explicit lower bound on the energy. The bonus of our direct approach based on Lieb and Yau's [13] strategy in the variant found in [6] -compared to transfering the methods of [14] -is our result on the positivity of the energy. (8) The numerical value of the critical coupling constant is Z c ≈ 0.3780 which is compared with the expected critical coupling constantZ c of the existence of a distinguished self-adjoint extension of the non-magnetic Weyl operator W Z .…”
Section: Notation Formulation Of the Problem And Main Resultsmentioning
confidence: 99%